Pengembangan LKS Berbasis PMRI Menggunakan Konteks Etnomatematika pada Materi SPLDV - Rini Prabawati; Yufitri Yanto; Novianti Mandasari (Jurnal Pendidikan Matematika:Judika Education, 2019)
The purpose of this study was to develop a realistic worksheet using the Ethnomatematics on SPLDV material and to determine the quality of worksheets in terms of validity and practicality. The method used in this study is the Research and Dependency (R&D) method which is a developmental study referring to the 4-D development model, namely define, design, develop, and disseminate modified to 3-D. The instruments used to measure the quality of worksheets that were developed include validation sheets, and practicality questionnaires. The product of this research is a realistic worksheet using ethnomatematics context on SPLDV material with the advice of eighth grade students of junior high school. The results showed that: (1) the quality of worksheets seen from the validity aspects included in the valid category with an overall average score of 3.06; and (2) the quality of worksheets seen from the practical aspect is categorized very practical with an overall average score of 3.5. Conclusion, the development of PMRI-based worksheets in the context of ethnomatematics in SPLDV material was declared valid and practically used by students. Keywords: Ethnomatematics worksheet, PMRI, SPLDV